2020
DOI: 10.3390/w12040926
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Urban Flood on Traffic Disruption using Rainfall–Depth–Vehicle Speed Relationship

Abstract: The transportation network enables movement of people and goods and is the basis of economic activity. Recently, short-term locally heavy rains occur frequently in urban areas, causing serious obstacles to road flooding and increasing economic and social effects. Therefore, in advanced weather countries, many studies have been conducted on realistic and reliable impact forecasting by analyzing socioeconomic impacts, not just information transmission as weather forecasts. In this paper, we use the Spatial Runof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…As can be seen in Table 1 , most of the literature studied traffic conditions in Western countries, such as the United States [ 13 , 33 ], France [ 12 ], Spain [ 7 ], Greece [ 25 , 26 ], Australia [ 31 ], and Sweden [ 34 ]. A few studies reported on the main metropolises in Asia, such as Hong Kong [ 8 ], Beijing [ 15 ], Shenzhen [ 16 ], and Seoul [ 17 ]. All of the mentioned works were conducted based on modern cities in developed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Table 1 , most of the literature studied traffic conditions in Western countries, such as the United States [ 13 , 33 ], France [ 12 ], Spain [ 7 ], Greece [ 25 , 26 ], Australia [ 31 ], and Sweden [ 34 ]. A few studies reported on the main metropolises in Asia, such as Hong Kong [ 8 ], Beijing [ 15 ], Shenzhen [ 16 ], and Seoul [ 17 ]. All of the mentioned works were conducted based on modern cities in developed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, measuring vehicle speed in an urban area might need different technologies, such as wireless sensor networks. Although some researchers also focused on traffic studies on urban roads, all of those works considered the developed countries’ road condition, such as in South Korea [ 17 ], Sweden [ 33 ], the United States [ 35 ], Athens, Greece [ 25 ], and Thessaloniki, Greece [ 26 ]. In summary, each work mentioned above shows various weather impact with different precipitation and characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in environmental quality in the Urip Sumoharjo-Perintis Kemerdekaan road corridor has resulted in physical damage to the environment, urban flooding, disease transmission, and climate change. Urban flooding is the most frequent type; it is a serious obstacle to road users and impacts economic and social conditions [100][101][102][103]. Environmental quality degradation in the Urip Sumoharjo-Perintis Kemerdekaan road corridor is shown in Figure 11.…”
Section: Traffic Volume and Decreasing Environmental Qualitymentioning
confidence: 99%
“…The authors in Choo et al (2020) [9] stated that stormwater overflow from metropolitan advancement makes undesired effects surface waters which effect on roads and transportation operations, including release of toxins, disintegration, and loss of living space. A treatment train comprising of porous interlocking solid asphalt and underground stormwater reaping was observed to evaluate water quality enhancements.…”
Section: Introductionmentioning
confidence: 99%